Detailed investigation of the lesion formation with a novel contact force sensing catheter with a mesh‐shaped irrigation tip - Kazuhisa Matsumoto; Daisuke Kawano; Wataru Sasaki; Naomichi Tanaka; Masataka Narita; Hitoshi Mori; Kenta Tsutsui; Yoshifumi Ikeda; Takahide Arai; Shintaro Nakano; Ritsushi Kato; Kazuo Matsumoto (Journal of Arrhythmia, 2023)
Abstract Background Recently, a novel contact force (CF) sensing catheter with mesh‐shaped irrigation tip (TactiFlex SE, Abbott) was invented and is expected to be useful for safe and effective radiofrequency ablation. However, this catheter's detailed characteristics of the lesion formation are unknown. Methods With an in vitro model, TactiFlex SE and its predecessor, FlexAbility SE, were used. A cross‐sectional analysis of 60 s lesions (combination of various energy power settings [30, 40, and 50 W], and CFs [10, 30, and 50 g]) and longitudinal analysis (combination of various powers [40 or 50 W], CFs [10, 30, and 50 g] and ablation times [10, 20, 30, 40, 50, and 60 s]) of both catheters were analyzed and compared. Results One hundred eighty RF lesions were created in protocol 1 and 300 in protocol 2. The lesion formation, impedance changes, and steam pops characteristics were similar between the two catheters. Higher CFs were related to higher incidences of steam pops. A nonlinear, time‐dependent increase in the lesion depth and diameter was observed for all power and CF settings, and linear, positive correlations between the RF delivery time and lesion volume were observed for all power settings. Compared with 40 W, a 50 W ablation created greater lesions. Longer durations with higher CF settings had a higher steam pop incidence. Conclusions The lesion formation and incidence of steam pops with TactiFlex SE and FlexAbility SE were similar. A 40 or 50 W ablation with careful CF control not to exceed 30 g in addition to monitoring impedance drops was required to safely create transmural lesions.